Peristiwa Ketidakpastian Pada Pelaksanaan Tol Layang A.P.Pettarani Seksi III Kota Makassar - Rebecca S Tambunan; Helen A.I. Sopacua; Josefine E Latupeirissa (Paulus Civil Engineering Journal, 2020)
The A. P. Pettarani elevated toll road is a project construction which is takes a long time and complex that can be create uncertainties that will eventually present a wide range of risks. The impact of these risks can affect productivity, performance, quality, and project cost budgets. The success of the construction project depends lagerly on the ability of the project manager to manage the risks involved. Risk management includes the steps involved in executing risk management planning, identification, responses, reaction, and monitoring of a project. Therefore, research was conducted to identify, analyze, and to knowing dominant risks responses, using the primary data collection method of questionnaire using the likert scale, probability x impact matrix, risk map, and interview, which is in this research have eleven dominant risk variables found in the project.